An Integrated Literature Review of Death Education in Pre-Registration Nursing Curricula: Key Themes. (2nd January 2014) - Cavaye, Joyce; Watts, Jacqueline H.
Abstract : Recent policy has raised the profile of end-of-life care internationally, with the aim of increasing access to quality care for everyone experiencing life-limiting illness. This reflects an international shift in the provision of palliative care to encompass chronic conditions other than cancer. Nurses have an important role in delivering this care and need to be equipped with particular knowledge and skills. However, pre-registration nursing curricula have traditionally had a limited emphasis on death and dying and nurses report feeling unprepared to care for dying patients. This has led to claims that death education in pre-registration curricula is inadequate. This integrated review explores the published literature that reports on death education within pre-registration nurse education. Presenting an international overview, the aim of the review is to contribute to knowledge about the nature and extent of death education in pre-registration curricula. In the context of this paper, death education encompasses both palliative and end-of-life care. Electronic searches of major bibliographic databases found inconsistencies across educational provision with variations in quantity, content, and approach. Despite an increasing amount of death education in pre-registration curricula, there remains a deficit in key areas such as knowledge, skills, organisation of care, and teamwork.